Enhancing Political Awareness and Participation in Rural Communities: A Case Study of KKN Program in Asilulu, Indonesia - Fransina Latumahina; Ayu Andira Sultan; Alfian Hulihulis; Alwi Alwi (Universitas Muhammadiyah Sidoarjo, 2023)
This research investigates the effectiveness of the Real Work Lecture (KKN) program in increasing political awareness and participation among rural communities in Asilulu, Indonesia. The study aims to address the lack of political education and the prevalence of electoral fraud and voter apathy in the region. Through a community-based approach, the KKN program implemented various methods such as counseling, training, socialization, and group assistance. The study utilized qualitative data collected from government officials and community members, indicating a positive response and high active participation. The results highlight the success of the program in promoting a positive political narrative and combating practices such as money politics and abstention. The implications of this study contribute to the development of effective strategies for political education and encourage greater citizen engagement in political processes. Highlight: Community empowerment through Real Work Lecture (KKN) program Importance of political education in rural communities Promoting positive political narratives through socialization Keyword: Real Work Lecture, Community Empowerment, Political Education, Socialization, Active Citizen Engagement